Ric-8A, a Gα protein guanine nucleotide exchange factor potentiates taste receptor signaling - Fenech, Claire J.; Patrikainen, lila; Kerr, Daniel S.; Grall, Sylvie; Liu, Zhenhui; Laugerette, Fabienne; Malnic, Bettina; Montmayeur, Jean-Pierre (Frontiers in Cellular Neuroscience, 2009)
Taste receptors for sweet, bitter and umami tastants are G-protein coupled receptors (GPCRs). While much effort has been devoted to understanding G-protein-receptor interactions and identifying the components of the signalling cascade downstream of these receptors, at the level of the G-protein the modulation of receptor signal transduction remains relatively unexplored. In this regard a taste-specific regulator of G-protein signaling (RGS), RGS21, has recently been identified. To study whether guanine nucleotide exchange factors (GEFs) are involved in the transduction of the signal downstream of the taste GPCRs we investigated the expression of Ric-8A and Ric-8B in mouse taste cells and their interaction with G-protein subunits found in taste buds. Mammalian Ric-8 proteins were initially identified as potent GEFs for a range of Gα subunits and Ric-8B has recently been shown to amplify olfactory signal transduction. We find that both Ric-8A and Ric-8B are expressed in a large portion of taste bud cells and that most of these cells contain IP3R-3 a marker for sweet, umami and bitter taste receptor cells. Ric-8A interacts with Gα-gustducin and Gαi2 through which it amplifies the signal transduction of hTas2R16, a receptor for bitter compounds. Overall, these findings are consistent with a role for Ric-8 in mammalian taste signal transduction.